Globalization and South Asia - Vanaik, Achin (ed.) (New Delhi, 2004)
This book brings together acknowledged experts in their respectivefields to provide a uniquely authoritative and comprehensiveperspective on globalization and its impact on South Asiagenerally, and on India in particular. It covers a wide range ofissues both economic and beyond. Apart from area studies of Nepal,Sri Lanka, Pakistan, Bangladesh and India, other issues taken upfor study include the World Trade Organization as well as theimpact of globalization on science and technology, the environment,the media, education, culture, health, feminist publishing,communalism and international relations.
Keywords: Economic development